Molecular epidemiology of norovirus associated with acute gastroenteritis in Taizhou, China: A retrospective study - Weiwei Shen; Ying Sheng; Jian Weng; Guixia Li; Donghong Wang; Danhong Qiu; Ye Lu; Haijiang Lin (Elsevier, 2020)
Background: Norovirus (NoV) is recognized as a leading global cause of viral acute gastroenteritis (AGE). To better understand the prevalence and genotypic patterns of NoV infection in Southeast China, we conducted a retrospective study of diarrheal syndrome surveillance of NoV and analyzed the epidemiological characteristics of AGE cases and phylogenetic evolution of NoV strains. Methods: 1464 AGE patients in two diarrhea surveillance sentinel hospitals were sampled during 2016 and 2017. NoV Positive samples were genotyped by ORF1/ORF2 overlapping regional gene sequencing. Sequences analyses of the NoV genotypes were confirmed by online NoV Genotyping Tool and the phylogenetic analysis was constructed by MEGA 7.0. Results: 139 (9.49%) of the AGE specimens were NoV positive. The GII strain was the main geno-group in NoV infected patients. At least 12 NoV genotypes and seven recombinant strains were detected. Major NoV genotypic transformations were GII.Pe/GII.4, GII.P17/GII.17 and GII.Pe/GII.17 in 2016 to GII.P16/GII.2, GII.P17/GII.17 and GII.Pe/GII.4 in 2017. Phylogenetic analysis showed that GII.P16/GII.2 recombinant strains clustered with those detected in the USA, Russia and Japan in 2016. Conclusion: We characterized the molecular epidemiology of NoV infection in AGE patients during 2016-2017. The main three NoV GII genotypes circulating in the population of Taizhou were GII.P17/GII.17, GII.Pe/GII.4 and GII.P16/GII.2.The GII.P16/GII.2 genotype has become the predominant strain since first quarter 2017. Monitoring of the NoV genotypic shift is important for the prevention and control of AGE. Keywords: Molecular epidemiology, Norovirus, Acute gastroenteritis, Genotype